The Relationship Between Quality of Health Services with Patient Satisfaction in Private Hospital in West Java - Irianto, Gunawan; Abdilah, Asep Dian; Suhat, Suhat; Kurnia, Zhafirah; Mauliku, Novie Elvinawaty (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Quality of health services refers to the level of perfection provided by a hospital, and poor service quality can lead to dissatisfied patients and decreased patient visits. This study was to analyze the relationship between service quality and satisfaction of inpatients at RH Purwakarta Hospital. Methods: The research approach included a cross-sectional study, incorporating factors such as service quality (including characteristics of reliability, responsiveness, assurance, empathy, and physical evidence) and satisfaction. The research sample consisted of 99 inpatients from RH Purwakarta Hospital, selected using an incidental sampling technique. A questionnaire was utilized as the instrument. The analysis employed the chi-square test with a significance threshold of 95%. It involved paramedical professionals and other personnel, as mentioned by Aryanti et al. (2022). Results: The results of the analysis indicate that the contentment of inpatients at RH Purwakarta Hospital is correlated with the quality of health services (pvalue= 0,0001). Therefore, it is possible to infer that an individual's satisfaction with the quality of service will be influenced by their interest in receiving treatment at that particular service location in the future. Conclusions: Research indicates that service quality significantly impacts patient satisfaction, highlighting the need for RH Purwakarta hospital to enhance service standards to boost patient visits and loyalty.